2009
DOI: 10.1017/s1461145709990794
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive α2-adrenoceptor blockade enhances the antipsychotic-like effect of risperidone and facilitates cortical dopaminergic and glutamatergic, NMDA receptor-mediated transmission

Abstract: Compared to both first- and second-generation antipsychotic drugs (APDs), clozapine shows superior efficacy in treatment-resistant schizophrenia. In contrast to most APDs clozapine possesses high affinity for alpha2-adrenoceptors, and clinical and preclinical studies provide evidence that the alpha2-adrenoceptor antagonist idazoxan enhances the antipsychotic efficacy of typical D2 receptor antagonists as well as olanzapine. Risperidone has lower affinity for alpha2-adrenoceptors than clozapine but higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…In addition, the prefrontal dopamine output induced by these APDs was markedly enhanced by idazoxan (Hertel et al, 1999;Marcus et al, 2009;Wadenberg et al, 2007). Furthermore, to a similar magnitude as that of clozapine, idazoxan enhanced the effects of both raclopride and risperidone on prefrontal NMDA receptor-mediated transmission, an effect that has been shown to be dopamine-dependent and executed through the dopamine D 1 receptor (Chen and Yang, 2002;Marcus et al, 2005Marcus et al, , 2009. The increased prefrontal availability of catecholamines induced by adjunctive treatment with idazoxan is probably due to a co-release of dopamine and norepinephrine that is controlled by a 2 -adrenoceptors located on norepinephrine nerve terminals (Devoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prefrontal dopamine output induced by these APDs was markedly enhanced by idazoxan (Hertel et al, 1999;Marcus et al, 2009;Wadenberg et al, 2007). Furthermore, to a similar magnitude as that of clozapine, idazoxan enhanced the effects of both raclopride and risperidone on prefrontal NMDA receptor-mediated transmission, an effect that has been shown to be dopamine-dependent and executed through the dopamine D 1 receptor (Chen and Yang, 2002;Marcus et al, 2005Marcus et al, , 2009. The increased prefrontal availability of catecholamines induced by adjunctive treatment with idazoxan is probably due to a co-release of dopamine and norepinephrine that is controlled by a 2 -adrenoceptors located on norepinephrine nerve terminals (Devoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Its target optimization included D 2 partial agonism with low intrinsic activity, 5-HT 1A partial agonism, and antagonism at 5-HT 2A , a 1B -and a 2C -adrenergic receptors (Maeda et al, 2014), supporting a favorable antipsychotic profile with low EPS risk and potential to treat core symptoms in schizophrenia, including cognitive deficits (Arnt and Skarsfeldt, 1998;Drouin et al, 2002;Marcus et al, 2010;Newman-Tancredi and Kleven, 2011;Sallinen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a 2A -adrenoceptors, which are widely distributed in the brain, a 2C -adrenoceptors are predominantly located in the striatum (Scheinin et al, 1994;Uhlén et al, 1997;Fagerholm et al, 2008). Animal experiments and clinical studies have demonstrated that the therapeutic effect of an antipsychotic drug can be enhanced by the addition of idazoxan or mirtazapine, drugs that block a 2C -and a 2A -adrenoceptors (Litman et al, 1996;Hertel et al, 1999;Wadenberg et al, 2007;Joffe et al, 2009;Marcus et al, 2010). Antipsychotics such as clozapine, olanzapine, risperidone, and quetiapine exhibited higher affinities for a 2C -over a 2A -adrenoceptors (Kalkman and Loetscher, 2003;Kroeze et al, 2003).…”
Section: Discussionmentioning
confidence: 99%